THE COVID-19 PANDEMIC AND ITS IMPLICATIONS IN THE AGREEMENT - Sudarna, Niluh Yamuna Santhi; Tanaya, Putu Edgar (Kertha Semaya : Journal Ilmu Hukum; Vol 11 No 1 (2022)DO - 10.24843/KS.2022.v11.i01.p13, 2023)
The aim of writing this journal is to provide new knowledge regarding the provisions of force majeure in the agreement if in the future there are circumtances beyond human control that have never happened which resulted in the parties involved in the agreement being unable to carry out theit obligations. The research method in this journal uses normative law, which uses two sources of legal material, namely, primary legal material, such as laws and regulations, and secondary legal materials, such as other related journals. The result of this journal is that the Covid-19 pandemic cannot simply be entered into a force majeure, because a force majeure is a situation beyond human control which causes one or both parties to be unable to carry out their obligations, if both parties can still carry out their obligations, the Covid-19 pandemic cannot be entered into a force majeure. However, if the government declares the spread of Covid-19 pandemi which is a non-natural disaster is a national disaster, then it has the potensial to be used as an excuse for force majeure. However, the government cannot determine a situation as a force majeure, the authorities lies with the judges through their considerations after assessing the contents of the agreement and the circumstances that occurred at that time based on the exisiting law and/or norms.